Amphoteric Surfactants as Flotation Collectors - R. W. Smith; R. Haddenham; C. Schroeder (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
Amphoteric surfactants are heteropolar organic compounds which possess at least two functional (ionic) oppositely charged groups per molecule. The ones studied are manufactured by General Mills and possess one or more long hydrocarbon chains plus a carboxyl group (s) and an amino or imino group. Hallimond tube and M. C. Fuerstenau micro flotation cell flotation tests were performed on quartz and hematite as a function of pH using amphoteric, cationic, and anionic surfactants as collectors. For the most part, flotation could be correlated with an interaction of charged groups on the collectors with oppositely charged sites on the minerals plus association of hydrocarbon chains. The comparison of flotation in a Hallimond tube and an M.C. Fuerstenau cell shows that one should use care in using the latter if one excludes an additional frother from the system. Also, it is interesting to note that sometimes greater collector concentrations are required in the Fuerstenau cell for comparable flotation recoveries.